Maternal postpartum bonding impairment and increased substance use to cope with pandemic-related stress - Roland, Alysa; Dressler, Caitlin M.; Shreffler, Karina M. (Frontiers in Psychology, 2024)
Substance use rates, particularly among women, increased substantially during the COVID-19 pandemic. Psychological and economic risks disproportionately experienced by women were associated with increase in substance use patterns during the pandemic. Using substances (i.e., tobacco, alcohol, cannabis) to cope with stress is well-documented; what is less known are protective factors that were associated with less substance use during the pandemic. We examined whether mothers of young children (N=96) who reported postpartum bonding impairment before the start of the pandemic reported greater substance use during the pandemic as a means to cope. Results from linear regression analyses found that mothers who reported higher levels of pre-pandemic mother-infant bonding impairments reported greater use of alcohol and other substances as a means to cope with pandemic stressors. These findings suggest that social connections might be a strategy to reduce substance use as a maladaptive coping behavior, especially during widespread crises such as the recent pandemic or for mothers of young children. In particular, promoting postpartum bonding through interventions might help to reduce substance use among new mothers.